The moisture-triggered controlled release of a natural food preservative from a microporous metal–organic framework. Issue 10 (22nd December 2015) - Wang, Hao; Lashkari, Elham; Lim, Hyuna; Zheng, Chong; Emge, Thomas J.; Gong, Qihan; Yam, Kit; Li, Jing
Abstract : In this work we demonstrate that allyl isothiocyanate (AITC), a common food flavoring agent and food preservative, can be effectively captured by and released in a controlled manner from a microporous metal–organic framework (MOF). Abstract : In this work we demonstrate that allyl isothiocyanate (AITC), a common food flavoring agent and food preservative, can be effectively captured by and released in a controlled manner from a microporous metal–organic framework (MOF). The extent of AITC–MOF interactions is quantitatively measured by orbital overlap population calculations. Controlled release experiments show that loaded AITC can be released by applying higher relative humidity. Further analysis reveals that the underlying mechanism of the controlled release is associated with the transformation of the MOF from a porous to a nonporous structure at high humidity. This study represents the first example of making use of MOF porosity in food preservation.